The Louisiana Teacher Assault Pay Statute| An Analysis of Court Decisions Interpreting the Statute and a Comparative Study of Teacher Assault Pay Statutes in Other States - Wright, Michael W. (University of Louisiana at Lafayette, 2017)
Municipalities, administrators, and teachers have faced the challenge of school violence since public education began. In some states, legislatures have passed special legislation granting specific benefits to teachers who are injured by violence while on duty. Louisiana’s teacher assault pay statute provides that a teacher who is away from work due to an assault by a student or other person is entitled to full pay without any deductions from the teacher’s accumulated sick leave. However, the meaning of that statute has been disputed in litigation between teachers who suffered injuries and Louisiana school boards that seek to limit their responsibility for paying teachers who are on leave due to workplace violence. As a matter of public policy, teachers who are injured in the workplace by acts of violence should receive special compensation, whether the violence was perpetuated by a student or any other person. And teachers who are harmed by a violent incident deserve special compensation whether or not the teacher was the intended victim of a violent act. This study analyzed Louisiana appellate court decisions that interpreted the Louisiana teacher assault pay statute, as well as the teacher assault statutes that have been adopted in twelve other states. Based on this analysis, the researcher drafted a proposal for a model teacher assault pay statute that codifies the public policy considerations in favor of compensating teachers for injuries caused by workplace violence. The model statute grants injured teachers up to one year’s compensation without reduction in accumulated sick leave, and the statute clarifies that a teacher victimized by violence is entitled to the benefits of the teacher assault pay statute, regardless of whether the teacher was the intended victim.